KERAMIK (ADVANCE CERAMICS) SEBAGAI MATERIAL ALTERNATIF DI BIDANG KESEHATAN - Arifin, Fatahul; Satria Martomi, Eka (AUSTENIT, 2009)
Ceramics are non-metal material and are able to meet in daily activities. Generally, ceramic have superior high temperature strength, higher hardness, lower density and lower thermal conductivity than metal. The disadvantages of ceramics as structural materials are flaws, such as cracks, voids, and inclusions. In development of ceramics can be used in medical field for instance, implant of bone or tissue of the body. Hydroaxyapatite (HAp) is one of ceramics that is applied in medical field. In natural resources HAp is easy to find in every place in the world. The advantage of ceramics is bio- comfortable and disadvantages is poor fatigue properties, this material cannot be used in bulk form fro load bearing application such as orthopedics.